Double mutant fibrillin-1 (FBN1) allele in a patient with neonatal Marfan syndrome. Issue 9 (September 1996) - Wang, M; Kishnani, P; Decker-Phillips, M; Kahler, S G; Chen, Y T; Godfrey, M
Abstract : It is now well established that defects in fibrillin-1 (FBN1) cause the variable and pleiotropic features of Marfan syndrome (MFS) and, at the most severe end of its clinical spectrum, neonatal Marfan syndrome (nMFS). Patients with nMFS have mitral and tricuspid valve involvement and aortic root dilatation, and die of congestive heart failure, often in the first year of life. Although mutations in classical MFS have been observed along the entire length of the FBN1 mRNA, mutations in nMFS appear to cluster in a relatively small region of FBN1, approximately between exons 24 and 34. Here we describe the appearance of two FBN1 mutations in a single allele of an infant with nMFS. The changes were within six bases of each other in exon 26. One was a T3212G transversion resulting in an I1071S amino acid substitution and the second was an A3219T transversion resulting in an E1073D amino acid substitution. This is the first reported double mutant allele in FBN1.